Associations of Sleep Disorders With Depressive Symptoms in Early and Prodromal Parkinson’s Disease - Ma, Jiangnan; Dou, Kaixin; Liu, Ruize; Liao, Yajin; Yuan, Zengqiang; Xie, Anmu (Frontiers in Aging Neuroscience, 2022)
Background: Non-motor symptoms, including sleep disorders and depression are common in Parkinson’s disease (PD). The purpose of our study is to explore the effect of sleep disorders, including the probable rapid-eye-movement (REM) sleep behavior disorder (pRBD) and the daytime sleepiness, on depressive symptoms in patients with early and prodromal PD. Methods: A total of 683 participants that obtained from the Parkinson Progression Markers Initiative (PPMI) were included, consisting of 423 early PD individuals, 64 prodromal PD individuals and 196 healthy controls (HCs), who were followed up to five years from baseline. Multiple linear regression models and linear mixed effects models were conducted to explore the relationship between sleep disorders and depression at baseline and longitudinally, respectively. Multiple linear regression models were used to further investigate the association between the change rates of daytime sleepiness score and depression-related score. Mediating effect analyses were also performed. Results: At baseline analysis, early and prodromal PD individuals, who had higher RBD screening questionnaire (RBDSQ) score, or who were considered as pRBD, or who manifested specific behaviors of RBD (things falling down when sleep or disturbance of sleep), showed significantly the higher score of depression-related questionnaires. Our 5-year follow up study showed that sleep disorders, including pRBD and daytime sleepiness were associated with the increased depressive-related score in early and prodromal PD individuals. Interestingly, we also found that the increased possibilities of daytime sleepiness were associated with depressive-related score. Finally, mediation analysis demonstrated the relationship between RBD and depressive symptoms was partially mediated by autonomic symptoms, such as postural hypertension, salivation, dysphagia and constipation. Conclusions: Our study shows that sleep disorders, including pRBD and daytime sleepiness, are associated with depression at baseline and longitudinally, which is partially mediated by the autonomic dysfunction in early and prodromal PD, with an implication that sleep management is of great value for disease surveillance.